2019
DOI: 10.1111/nbu.12361
|View full text |Cite
|
Sign up to set email alerts
|

Improving wheat as a source of iron and zinc for global nutrition

Abstract: Wheat is the staple food crop in temperate countries and increasingly consumed in developing countries, displacing traditional foods. However, wheat products are typically low in bioavailable iron and zinc, contributing to deficiencies in these micronutrients in countries where wheat is consumed as a staple food. Two factors contribute to the low contents of bioavailable iron and zinc in wheat: the low concentrations of these minerals in white flour, which is most widely consumed, and the presence of phytates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
65
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 35 publications
5
65
3
Order By: Relevance
“…Crude fiber was increased remarkably by combined solution with a 60% Zn + 40% Fe ratio as well as other ratios. This could be possibly linked with a significant accumulation of Zn and Fe in aleurone, endosperm, and embryo [22,27] when these micronutrients are supplied to wheat, as discussed in different literature [13,22,74]. It can also be a result of assimilates remobilization in which process Zn and Fe have a greater role.…”
Section: Crude Fibermentioning
confidence: 92%
See 2 more Smart Citations
“…Crude fiber was increased remarkably by combined solution with a 60% Zn + 40% Fe ratio as well as other ratios. This could be possibly linked with a significant accumulation of Zn and Fe in aleurone, endosperm, and embryo [22,27] when these micronutrients are supplied to wheat, as discussed in different literature [13,22,74]. It can also be a result of assimilates remobilization in which process Zn and Fe have a greater role.…”
Section: Crude Fibermentioning
confidence: 92%
“…Recently, it was reported that in the UK, the Zn intake of about a quarter of adolescents is below the lower reference nutrient intake (LRNI) and the Fe intake of over half of all adolescent girls and over a quarter of adult women is below the LRNI [13,14]. Nutrient-deficient food and diet related problems are the main cause of death on Earth, and this can be prevented by supplying nutrients in a sustainable manner, and finding solutions to malnutrition [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phytic acid (myo-inositol 1,2,3,4,5,6-hexakisphosphate, InsP 6 ) is the main phosphorus reservoir in plant tissues, which, in the form of phytate salts, complexes with proteins and carbohydrates, and is considered as an antinutritional factor [10,11]. Phytate, as the compound that reduces the bioavailability of minerals, protein, and starch, may exert a negative effect on mashing and fermentation processes.…”
Section: Introductionmentioning
confidence: 99%
“…Phytate, as the compound that reduces the bioavailability of minerals, protein, and starch, may exert a negative effect on mashing and fermentation processes. It decreases starch degradation and the available spectrum of fermentable sugars mainly by chelating Ca 2+ and lowering α-amylases activity, inhibits protease, and reduces free amino acid release, as well as chelates cofactors like Mg 2+, Zn 2+ ions, which are crucial for proper Saccharomyces cerevisiae fermentation [9,10,12]. Only limited phytate dephosphorylation may occur by means of thermal hydrolysis, e.g., during cooking, and therefore, enzymatic decomposition seems to be the only effective treatment.…”
Section: Introductionmentioning
confidence: 99%